Modified subtotal laryngectomy with formation of a tracheopharyngeal shunt for locally advanced cancer of the larynx and hypopharynx - E. N. Malysheva; D. E. Kulbakin; E. L. Choynzonov; E. A. Krasavina (Сеченовский вестник)
Aim. To study the effectiveness of modified subtotal laryngectomy with the formation of a tracheopharyngeal shunt in patients with locally advanced cancer of the larynx and laryngopharynx.Materials and methods. We conducted a cohort study on the use of combined treatment (surgical and radiation/ polychemotherapy) in 25 patients: 24 men, 1 woman; median age – 56 years. The subtotal laryngectomy technique that we developed and used included the preservation of one arytenoid cartilage, the posterior third of the vocal fold, and the recurrent nerve on the side not affected by the tumor. We studied postoperative complications, the length and diameter of the tracheopharyngeal shunt, the functioning of the arytenoid cartilage, the frequency of voice recovery and its quality, and overall and relapse-free survival.Results. In the postoperative period, 8 (32%) patients developed a pharyngocutaneous fistula; tracheal stenosis after tracheostomy was observed in 8 (32%) cases. The length of the tracheopharyngeal shunt varied from 16.4 to 25.6 mm, in all cases its course was tortuous, the diameter of the preserved part of the vocal fold varied from 1.1 to 1.5 mm. 24 (96%) patients demonstrated the functioning of the arytenoid cartilage and its work as a valve. Voice function recovered in 24 (96%) patients. Fundamental frequency was 155.3 ± 20.9 Hz, maximum phonation time of the vowel “A” – 3.5 ± 1.0 s, duration of pauses in phrase – 0.24 ± 0.03 s, speech rate – 99.8 ± 8.4 words/ min, number of words in phrase 6.5 ± 0.3. The average value of the Acoustic Voice Quality Index was 6.74, which indicates dysphonia (for the Russian language, the threshold value for dysphonia is 4.86), but this did not interfere with patients’ communication at home and on the phone. Overall and relapse-free survival at 1, 2, and 3 years were 100%, 89%, 78% and 86%, 78%, 72%, respectively.Conclusion. The method of operation proposed by us contributes to the restoration of voice function in the majority of patients with oncological outcomes comparable to total laryngectomy.